Clinical effect of Nirgundi Patra pinda sweda and Ashwagandhadi Guggulu Yoga in the management of Sandhigata Vata (Osteoarthritis) - Joshi, Alpesh (Medknow Publications & Media Pvt Ltd, 2011)
Sandhigata Vata is one among the 80 Nanatmaja Vata Vyadhies. Sandhigata Vata and Osteoarthritis have common symptoms, and hence, both are considered as similar entities by a majority of Ayurvedic scholars and same has been adopted here. Osteoarthritis is the most common joint disease among human beings today. In this study, a total of 116 patients were registered, out of them 101 patients had completed the full course of treatment, while 15 patients left against medical advice. The 101 patients of Sandhigata Vata were treated in two groups. Group A: In this group 50 patients of Sandhigata Vata were treated with Nirgundi Patra pinda sweda for 21 days and Ashwagandhadi Guggulu Yoga3 g/day for 45 days was given orally. Group B: In this group 51 patients of Sandhigata Vata were treated with only Ashwagandhadi Guggulu Yoga 3 g/day for 45 days. To assess the effect of the therapy objectively, all the signs and symptoms of Sandhigata Vata were given a score, depending upon their severity. Also functional tests like walking time, climbing stairs, and joint movement, were measured as a criteria for assessment. Both the groups showed good results, but Group B showed better results in comparison to group A